What ‘s wrong with the Asian and African Students’ mathematics learning achievement? The multilevel PISA 2015 data analysis for Indonesia, Japan, and Algeria - Kartianom Kartianom; Oscar Ndayizeye (Jurnal Riset Pendidikan Matematika, 2017)
This research aims at knowing the factors, involving both students and school levels, related to the math learning achievement for students in Indonesia, Japan, and Algeria by using PISA 2015 data. The sample in this study consists of students from three countries that took part in PISA 2015. The three countries chosen are Indonesia, Japan, and Algeria, each respectively having as participants 5.800, 6.411, and 4.460. the findings showed that the sense of belonging of students towards mathematics, the socio-economic status of their families, and the average of school’s social-economic status can predict significantly the students’ math learning achievement for the Indonesia and Japan, while for the Algerian students the socio-economic status is statistically insignificant in predicting their math learning achievement. The outcome of this analysis support the idea that the school attended plays a big role as far as mathematics learning achievement is concerned. To conclude, it should be summed up that the affective characteristics (sense of belonging of students), family background (students’ socio-economic status), and the variable school-level (average socio-economic status of schools) can be among students as far as mathematics learning achievement is concerned.